Răspuns :
1+(15-4xa+9/3)/6=2
(15-4xa+3)/6=1
15-4xa+3=6
15-4xa=3
4xa=12
a=3
(15-4xa+3)/6=1
15-4xa+3=6
15-4xa=3
4xa=12
a=3
1+(15-4*a+9:3):6=2
1+(15-4*a+9:3):6-(2)=0
((15-4a)+3)
(1+------------------) -2=0
6
18-4a
--------
6
18-4a=-2*(2a-9)
(9-2a)
(1+-----------) -2=0
3
1 1*3
1=--- = ------
1 3
3+(9-2a) 12-2a
------------ = ---------
3 3
(12-2a)
---------- -2=0
3
2 2*3
2=----= ------
1 3
12-2a = -2*(a-6)
-2*(a-6)-(2*3) 6-2a
------------------- = --------
3 3
6-2a= -2*(a-3)
-2(a-3)
--------- =0
3
-2*(a*3)
---------- *3=0*3
3
12*(a-3)=0
-2=0
a-3=0
a=3
R=>a=3
1+(15-4*3+9:3):6=2
1+(15-4*a+9:3):6-(2)=0
((15-4a)+3)
(1+------------------) -2=0
6
18-4a
--------
6
18-4a=-2*(2a-9)
(9-2a)
(1+-----------) -2=0
3
1 1*3
1=--- = ------
1 3
3+(9-2a) 12-2a
------------ = ---------
3 3
(12-2a)
---------- -2=0
3
2 2*3
2=----= ------
1 3
12-2a = -2*(a-6)
-2*(a-6)-(2*3) 6-2a
------------------- = --------
3 3
6-2a= -2*(a-3)
-2(a-3)
--------- =0
3
-2*(a*3)
---------- *3=0*3
3
12*(a-3)=0
-2=0
a-3=0
a=3
R=>a=3
1+(15-4*3+9:3):6=2